A Meta‐Analysis of 67 Studies with Presenting Symptoms and Laboratory Tests of COVID‐19 Patients. (6th November 2020) - Mair, Manish; Singhavi, Hitesh; Pai, Ameya; Singhavi, Jinesh; Gandhi, Prachi; Conboy, Peter; Baker, Andrew; Das, Sudip
Abstract : Objectives/Hypothesis: The objective of this meta‐analysis was to look at the pooled prevalence of symptoms, laboratory tests, and imaging of all COVID‐19 infected patients. This will allow better identification of potential COVID‐19 patients and take appropriate precautions. Study design: Meta analysis. Methods: We searched three databases, PubMed, EMBASE, and Ovid to identify studies published between Dec‐2019 and May‐2020. All studies reporting upper‐aerodigestive symptoms of COVID‐19 infection were included. The meta‐analysis was conducted following meta‐analyses of observational studies in epidemiology (MOOSE) guidelines, which have evaluated the pooled prevalence of 14 symptoms and nine laboratory investigations. Results: Based on inclusion criteria, 67 publications consisting of 8302 patients were included. Among adults, the pooled proportion of hypertensive and diabetic patients was 18% and 7%. Cough (53% [0.46–0.61]), anosmia (38% [0.19–0.58]), loss/distortion of taste (31% [0.17–0.45]), and nasal obstruction (26% [0.12–0.39]) were the most common ear, nose & throat (ENT) symptoms. Fever (69% [0.62–0.76]) and fatigue (31% [0.26–0.37]) were the commonest generalized symptoms. C‐reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were raised in 56% (0.41–0.71) and 49% (0.21–0.77), respectively. Interestingly, lymphopenia (41% [0.30–0.53]) and leucopenia (22% [0.16–0.29]) were more common than lymphocytosis (33% [0.02–0.64]) and leucocytosis (12% [0.09–0.16]). Fever (69% vs. 44%), cough (53% vs. 33%), and dyspnea (20% vs. 4%) were more common in adults as compared to the pediatric population. Diarrhea was more common among the pediatric cases (12%) versus (9%). The pooled estimate of fatality was 4%. Conclusions: The most commonly experienced ENT symptom was cough followed by anosmia and dysguesia. Raised ESR and CRP with leukopenia and lymphopenia are common laboratory findings. Majority of the infected patients had abnormal computed tomography findings. COVID infection is less severe in pediatric patients. Laryngoscope, 131:1254–1265, 2021